2016
DOI: 10.3390/v8120332
|View full text |Cite
|
Sign up to set email alerts
|

Equine Immunoglobulin and Equine Neutralizing F(ab′)2 Protect Mice from West Nile Virus Infection

Abstract: West Nile virus (WNV) is prevalent in Africa, Europe, the Middle East, West Asia, and North America, and causes epidemic encephalitis. To date, no effective therapy for WNV infection has been developed; therefore, there is urgent need to find an efficient method to prevent WNV disease. In this study, we prepared and evaluated the protective efficacy of immune serum IgG and pepsin-digested F(ab′)2 fragments from horses immunized with the WNV virus-like particles (VLP) expressing the WNV M and E proteins. Immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In addition, the expression of HSP70, one of the most important cellular defense mechanisms, is induced under stressful conditions such as infection 54 . Interestingly, HSP70, GSH-Px and total antioxidant capacity are significantly up-regulated in pigs and rats after PEDV infection 55 57 . A study found that Nrf2 may increase the expression of antioxidant related genes by acting on the antioxidant response element (ARE) in the gene promoter, therefore control abnormal oxidative stress 58 .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the expression of HSP70, one of the most important cellular defense mechanisms, is induced under stressful conditions such as infection 54 . Interestingly, HSP70, GSH-Px and total antioxidant capacity are significantly up-regulated in pigs and rats after PEDV infection 55 57 . A study found that Nrf2 may increase the expression of antioxidant related genes by acting on the antioxidant response element (ARE) in the gene promoter, therefore control abnormal oxidative stress 58 .…”
Section: Discussionmentioning
confidence: 98%
“…In support of such a mechanism of action, Ide‐cleaved specific anti‐streptococcal Abs were shown to maintain protective binding activity 23 and, albeit to a variable degree, also F(ab’) 2 fragments specific for other pathogens/toxins can retain their binding capacity. 24 , 25 , 26 , 27 However, for other serotypes like AAV8, only a mild and transient inhibition on liver transduction by IdeS‐cleavage products was observed at the NAb titre tested. Interestingly, in vitro data for the two serotypes revealed that the cleavage products have similar capacity to inhibit transduction.…”
Section: Discussionmentioning
confidence: 98%
“…F(ab′) 2 fragments, being bivalent, are easier to purify in large quantities and more able to penetrate deeper into the tissue than the IgG antibody [6], thus increasing the time for excretion from the blood. There are reports on using F(ab′) 2 fragments to prevent West Nile virus (WNV) [7], feline calicivirus [8], Middle East respiratory syndrome coronavirus (MERS-CoV) [9] and Ebola virus (EBOV) [10,11].…”
Section: Introductionmentioning
confidence: 99%